Pengaruh chitosan belangkas (Tachypleus gigas) nanopartikel terhadap celah antara berbagai jenis semen ionomer kaca dengan dentin - Henny Sutrisman; Trimurni Abidin; Harry Agusnar (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: The development of dental material restoration is regarded to be relevant to obtain a better bonding between dental structure and restorative materials. Glass ionomer cement (GIC) is a bioactive material. Resin-modified GIC (RMGIC) is an alternative to the conventional glass ionomer. Nowadays with nano technology, this material is available in nano particle glass ionomer form in order to enhance the bond strength between tooth structure and restoration. The use of the natural product in dentistry such as chitosan has increased widely. Chitosan is one of the natural materials that used to improve the bioactivity of the glass ionomer. studies showed that addition of chitosan high molecule to GIC can increase mechanical performance and capability and also as a catalyst to release fluoride ions. Purpose: This study was aimed to examine the effect of the addition of high molecular nanoparticle chitosan derived from horseshoe crab (Tachypleus gigas) on interface of RMGIC, nano RMGIC and the dentin surface. Methods: Nano particle chitosan was added to the restorative materials and then applied to the class I cavity of premolar and then the tooth was sectioned with diamond disc. specimens were prepared for sEM examination. Results: The result showed that the addition of chitosan increases adhesion between restoration and dentin structure. Conclusion: The addition of nanoparticle chitosan with a high molecular weight of 0.015% into RMGIC and nanoparticle RMGIC can improve the adhesion of restorative material to dentin structure.Latar belakang: Perkembangan restorasi bahan gigi untuk mendapatkan ikatan yang lebih baik antara struktur gigi dan bahan restoratif. semen ionomer kaca (sIK) adalah bahan bioaktif. semen ionomer kaca modifikasi resin (sIKMR) adalah sebuah alternatif untuk ionomer kaca konvensional. saat ini dengan teknologi nano, bahan ini tersedia dalam bentuk partikel nano ionomer kaca untuk meningkatkan kekuatan ikatan antara struktur gigi dan restorasi. Penggunaan produk alami dalam kedokteran gigi seperti kitosan telah meningkat banyak. Kitosan merupakan salah satu bahan alami yang digunakan untuk meningkatkan bioaktivitas dari ionomer kaca. studi menunjukkan bahwa penambahan molekul tinggi kitosan untuk GIC dapat meningkatkan kinerja mekanik dan kemampuan dan juga sebagai katalis untuk melepaskan ion fluoride. Tujuan: Penelitian ini bertujuan untuk menguji pengaruh penambahan kitosan nanopartikel molekul yang berasal dari kepiting tapal kuda (Tachypleus gigas) terhadap permukaan antara RMGIC, nano RMGIC dan permukaan dentin. Metode: Nano partikel kitosan ditambahkan pada bahan restoratif dan kemudian diterapkan pada kavitas kelas I premolar dan kemudian gigi tersebut dipotong dengan disc berlian. sampel disiapkan untuk pemeriksaan sEM. Hasil: Hasil penelitian menunjukkan bahwa penambahan kitosan meningkatkan adhesi antara restorasi dan struktur dentin. Simpulan: Penambahan nanopartikel kitosan dengan berat molekul tinggi 0,015% pada sIKMR dan sIKMR nano dapat meningkatkan adhesi bahan restorasi struktur dentin.